Karagraph computerized facial sketch - Dela Cruz, Jay V. (1998)
Identifying a person is still primary to investigations. When one runs out of evidences and proofs of identity of a certain person, the only choice left is to find an artist who will sketch the face of the person. The project that we are planning to implement aims to provide that of the artist's job: particularly facial sketch. Producing an image of the person would then be easier for any user since there are facial characteristics to choose from to which models pertaining to descriptions are displayed on screen for selection. Editing would be through the mouse device. Images can be enlarged, reduced and "morphed" to suit the user's desired illustration. New models of the features can be added to give the user a wider choice of images. Softwares almost the same to what we have envisioned are available aren't used because the models are mostly Caucasians. Editing is also hard and tiring, lacking editing tools such as flexible stretch mechanisms and "morphing". We would produce a similar software which will offer better sketching (e.g. stretch and compress of a particular part of the drawing and shade toning) also this will be applicable to an Asian setting, primarily the Philippines. The group has already achieved researching graphical algorithms from books and other resources. Our vision has changed from our idea of producing grayscale images only to colored ones although the team already estimated that we will not be dealing with three dimensional images. Though we still havent's been able to make a satisfying set of facial feature specifications or descriptions as we had discovered lately that we would need to consult cosmetic industries or any institution that sells facial beauty products.